The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000363743
|View full text |Cite
|
Sign up to set email alerts
|

Review of Frequency of Dysmenorrhea and Some Associated Factors and Evaluation of the Relationship between Dysmenorrhea and Sleep Quality in University Students

Abstract: Objective: To determine the frequency of dysmenorrhea in university students, review some associated factors and evaluate the relationship between dysmenorrhea and sleep quality. Material and Methods: The study group included 520 students. Survey forms prepared previously in line with the study objective were completed by the students under supervision. The severity of dysmenorrhea was rated with Visual Analogue Scale. Pittsburgh Sleep Quality Index was used to evaluate the sleep quality. The χ2 tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
(31 reference statements)
4
15
1
2
Order By: Relevance
“…In some studies, some forms of caffeinated drinks were assessed separately such as tea, coffee, Nescafe, but others studies assessed this group as whole. Seven studies [16,29,38,44,48,52,55] did not find any significant association between caffeine intake and dysmenorrhea, but Faramarzi and Salmalian [49], Pejčić and Jankovic [57], and Hailemeskel et al [56] found significant associations between caffeine consumption and higher intensity of menstrual pain. Drinking tea did not have a significant association with dysmenorrhea in 4 studies [28,43,45,60], but Wang et al [37] reported more tea consumption among women with dysmenorrhea.…”
Section: The Results Of the Selected Studies According To The Dietarymentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, some forms of caffeinated drinks were assessed separately such as tea, coffee, Nescafe, but others studies assessed this group as whole. Seven studies [16,29,38,44,48,52,55] did not find any significant association between caffeine intake and dysmenorrhea, but Faramarzi and Salmalian [49], Pejčić and Jankovic [57], and Hailemeskel et al [56] found significant associations between caffeine consumption and higher intensity of menstrual pain. Drinking tea did not have a significant association with dysmenorrhea in 4 studies [28,43,45,60], but Wang et al [37] reported more tea consumption among women with dysmenorrhea.…”
Section: The Results Of the Selected Studies According To The Dietarymentioning
confidence: 99%
“…It creates muscle spasm and pain in the menstrual cycle. Also, certain nutrients directly influence the circulation status of sexual steroids and cause muscle spasm [6,29,48,56]. The relationship between caffeine intake and dysmenorrhea has been reported in many studies due to its effect on vasoconstriction and pelvic pain [49].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Primary dysmenorrhea is considered as one of the main problems in women and in public health so that WHO refers to it as the main cause of chronic pelvic pain. 5 In fact, in addition to its huge economic burden, 6 dysmenorrhea affects different dimensions of life and causes limitations in daily activities 7,8 and low sleep quality, 9,10 as well as negatively affect the patient's mood, lead to depression, stress and anxiety. 8,11,12 Although the main cause of primary dysmenorrhea is not well recognized, most studies show an increase in the levels of prostaglandins E2α (PGE2α), F2α (PGF2α), and leukotriene during menstruation and this, in turn, results in more uterine muscle contractions and cramps.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) Dysmenorrhoea or painful menstruation is a condition known to commonly accompany the menstrual cycle especially in young females, characterized by painful abdominal cramps during the cycle, and may be frequently accompanied by other symptoms; sweating, headaches, nausea, vomiting, diarrhoea, tremor, weakness and fatigue, irritability and breast tenderness. (3)(4)(5) These symptoms can occur just before and/or early during menses, (6) and they last on average for two days. (3) Dysmenorrhoeal students have poorer sleep quality, (5) and an increased risk of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%